Information format in the calculation of probabilities by prospective primary school teachers - Fernandes, José António (2019)
In this article we study the calculation of probabilities performed by prospective primary school teachers, as well as the format of the information that they use in determining these probabilities. Fifty students, prospective primary school teachers, who were attending the second year of the Basic Education Degree course at a university in the north of Portugal participated in the study. Students were assigned several tasks of Probability and Statistics in a formal evaluation context. Only one of these tasks was studied, which involves several types of probability (simple, joint and conditioned probability) and two information formats (absolute frequencies and relative frequencies). In terms of the main obtained results, it is pointed out that the future teachers revealed a limited knowledge of probabilities and a clear preference for the use of the absolute frequencies in the calculation of these probabilities.